"Extension of the GSMW Formula in Weaker Assumptions". (30th April 2014) - Wang, Wenfeng; Chen, Xi
Abstract : In this note, the generalized Sherman-Morrison-Woodbury (for short GSMW) formula( A + Y G Z ∗ ) ⊙ = A ⊙ − A ⊙ Y ( G ⊙ + Z ∗ A ⊙ Y ) ⊙ Z ∗ A ⊙ is extended under some assumptions weaker than those used by Duan, 2013.